Extended abstracts spring 2013 : complex systems; control of infectious diseases - Deluca, Anna; Font-Clos, Francesc; Guerrero, Pilar; Korobeinikov, Andrei; Massucci, Francesco; Corral, Alvaro (Trends in Mathematics, 2014)
The two parts of this volume feature extended conference abstracts corresponding to selected talks given by participants at the "Joint CRM-Imperial College Workshop in Complex Systems" (seventeen extended abstracts) and "Emergence, Spread and Control of Infectious Diseases" (six extended abstracts), both held at the Centre de Recerca Matemàtica in Barcelona in spring 2013. Most of them are brief articles, containing preliminary presentations of new results not yet published in regular research journals. The articles are the result of a direct collaboration between active researchers in the area after working in a dynamic and productive atmosphere. Almost everything that is interesting and important for society is complex; here, examples scattered across the sciences are presented in order to illustrate the cross-disciplinary richness of state-of-the-art complex systems research: fracture avalanches and rain showers that mimic earthquakes; highly organized graphs that account for processes in neural networks, metabolic networks, food webs, or language; models for DNA dynamics; or statistical methods to test complexity in the form of structure on many different scales. In this context, mathematics is put to work to model the real system, and the models are kept at a minimum level so as not to interfere with understanding the essentials of the real system. The book is intended for established researchers, as well as for PhD and postdoctoral students who want to learn more about the latest advances in these highly active areas of research.